Forearm reactive hyperaemia is not mediated by nitric oxide in healthy volunteers - Nugent, A G (Blackwell Science Inc, 1999)
AIMS: To determine the role of nitric oxide (NO) in forearm reactive hyperaemia in healthy human subjects. METHODS: Ten healthy subjects aged 19–34 years underwent brachial artery cannulation. Forearm circulatory arrest was achieved by means of an upper arm cuff inflated to 200 mmHg for 5 min. The blood flow responses during reactive hyperaemia were measured using venous occlusion plethysmography following a 10 min intra-arterial influsion of 8 μmol min(−1)N-monomethyl l-arginine (l-NMMA) and following matching placebo administered in random order. Results were analysed by repeated measures anova and t-tests. RESULTS: l-NMMA resulted in a significant reduction of basal forearm blood flow indicating inhibition of basal NO release (P = 0.005). There was no significant difference between the blood flow responses during reactive hyperaemia following l-NMMA and placebo (P = 0.97). CONCLUSIONS: Nitric oxide production does not make a significant contribution to the vasodilatation associated with reactive hyperaemia in the human forearm.